PENGARUH DISIPLIN KERJA DAN KINERJA PETUGAS PUSKESMAS TERHADAP KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS JATIUWUNG KOTA TANGERANG TAHUN 2021 - Ningrum, Defi Setya; Imanuddin, Bayu (Nusantara Hasana Berdikari, 2021)
At the same time, the number of employees who have good discipline, morale, work assignments, punctuality and work efficiency will increase. This will support the achievement of quality targets for health services, employees and the community. Public health center discipline is said to be good, if there is an increase in discipline it becomes an important part of human resource management (HR), as an important factor in improving work. Research Objectives : to find out whether there is a influence of Work Discipline on the Quality of Health Services in 2021 and to find out whether there is a influence of the Performance of Officers Puskesmas on the Quality of Health Services in 2021. Research Methods : used in this study is a quantitative descriptive correlation to determine influence of Work Discipline and the Performance Puskesmas of Health Center Officers on the Quality of Health Services in 2021. Sampling was carried out using the Total Sampling technique, namely all Puskesmas employees, based on data at the Jatiuwung Health Center in 2021 with a population of 51 respondents. Based on the results of the T Test (Partial) research, it was found that the Variable influence of Work Discipline (Variable X1) and Officer Performance Puskesmas (Variable X2) on the Quality of Health Services (Variable Y) with a value of 0.000, and 0.024, which value is greater than = 0.05 and it can be concluded that all variables, namely the influence of work discipline (X1), officers' performance Puskesmas (X2) have a significant effect on the quality of health services (Y). Meanwhile, based on the results of the F (simultaneous) test that has been carried out, the value is 0.000 where the value is = 0.05, it can be concluded that these variables have a significant effect simultaneously.